Design fabrication and characterization of conductivity sensor using printed circuit board / Shaiful Bakhtiar Hashim - Hashim, Shaiful Bakhtiar (2009)
This paper described about design, fabrication and characterization of conductivity sensor using printed circuit board (PCB). The main objective is to sense the conductivity of aqua agriculture. A sensor was design by using interdigital capacitor concept where the term interdigital refers to pattern of fingers that is resembled by the shape and relative position of the electrodes. This sensor was fabricated by using PCB in order to minimize the cost than the existing conductivity sensor. Sensor performance was characterized by various test setups to check ability and accuracy of the sensor. From the result, it shown that the sensor has very good sensitivity with correlation coefficient R2 of 0.969.